Analisis Pendidikan Tauhid Dalam Perspektif Pemikiran Muhammad Bin Abdul Wahhab Dan Relevansinya Dengan Pendidikan Islam Kontemporer - Kamsi, Nurlila; Febriyeni, Marisa Deza; Ngimadudin, Ngimadudin (El-Ghiroh : Jurnal Studi Keislaman, 2021)
This study focuses on the concept of monotheism education based on the thoughts of Muhammad bin Abdul Wahhab. This study uses library research methods (Library Research). primary data sources which include books written by Muhammad bin Abdul Wahhab. Tawhid education according to Muhammad bin Abdul Wahhab, he classified monotheism into three parts, namely the monotheism of Rububiyah, the monotheism of Uluhiyah, and the monotheism of Asma` wa Nature. The relevance of monotheism education in Muhammad bin Abdul Wahhab's perspective with the current model of Islamic education. Meanwhile, Islamic education is currently changing the dualism system into scientific integration (general science and religious science) to create generations of Muslims who have intellectual intelligence in science and religion.